ARTIFICIAL INFECTION STUDY OF FASCIOLA GIGANTICA IN LOCAL SHEEP AND ITS IMPACT ON WEIGHT GAIN, HEMATOLOGY AND ENZYME GAMMA GLUTAMYL TRANSFERASE - Khajadatun Khajadatun; Wardiarto DP; Setyawan Budiharta (Jurnal Sain Veteriner, 1996)
This research was to investigate the effect of infection of Fasciola gigantica on weight gain, blood picture and the level of iiver damage of local sheep, and the correlation between the number of metacercariae infectH and the number of the fluke recovered.                                                                           Twenty male local sheep, were allocated randomly into 4 different groups. One group used as uninfected control and a total of 200, 500 and 1.000 metacercariae was infected into animals of groups 2, 3 and 4, respectively. Variables evaluated include weight gain, blood picture, gamma glutamyl tons/erase (GGTase) activity, and the number of egg and the fluke recovered. All individual sheep were weighed every week, whole blood and sera were taken every 3 weeks, fecal samples were started to b« examined 8 weeks after infection and every week thereafter. Weight gain, hematology picture and enzyme GGTase activity were anafized by split-plot, the number of egg and fluke recovered were analized by correlation. All sheep were killed 18 weeks after infection.                          The results show that infection F. gigantica causes norntocytic normochromic anemia in local sheep. Increased GGTase acitivity is observed. The number of fluke recovered correlates with the number of metacercariae infected.